A shea butter-based ketamine ointment: the antidepressant effects of transdermal ketamine in rats - Akan, Merve; Skorodumov, Ivan; Meinhardt, Marcus W.; Canbeyli, Resit; Unal, Gunes (Behavioural brain research, 2023)
The delayed onset of monoaminergic antidepressants and disadvantages of traditional administration routes created the need for alternative non-invasive delivery methods with rapid onset therapeutic effect. Ketamine attracted attention as a fast-acting glutamatergic antidepressant with ideal physiochemical properties for alternative routes of administration. However, there is no sufficient data for its transdermal use in depression. In this proof-of-concept study, we investigated the antidepressant effects of transdermal ketamine delivered via a novel ointment with skin protective, emulsifying and permeation enhancing properties. A shea butter-based 5% (w/w) ketamine ointment or a drug-free vehicle ointment were applied to the shaved dorsal skin of male Wistar rats for 2 days, twice a day. Behavioral despair, locomotor activity and anxiety-like behavior were respectively assessed in the forced swim test (FST), open field test (OFT), and elevated plus maze (EPM). The pharmacokinetic profile of the ointment was analyzed with high-performance liquid chromatography. Transdermal ketamine ameliorated behavioral despair without altering general locomotor activity and anxiety-like behavior, showing that skin-friendly drug carriers like shea butter may constitute promising alternatives to current routes of delivery for ketamine. Tested transdermal method aims to provide more sustainable drug delivery for long-term treatment schedules. Future studies can investigate its long-term use, side effects and abuse liability.